2017
DOI: 10.18535/jmscr/v5i2.133
|View full text |Cite
|
Sign up to set email alerts
|

Centchroman - A Magical Pill or a Myth

Abstract: MASTALGIA is a common symptom experienced by most of the females and most common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several Western pharmaceutical companies have been criticised for incomplete disclosure of trial designs (5). Vaccine approvals by the Indian drug regulator did not follow established pathways and decision-making processes were opaque (6). Chinese companies in particular have been criticised for only releasing partial trial results (7, 8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Western pharmaceutical companies have been criticised for incomplete disclosure of trial designs (5). Vaccine approvals by the Indian drug regulator did not follow established pathways and decision-making processes were opaque (6). Chinese companies in particular have been criticised for only releasing partial trial results (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…Several Western pharmaceutical companies have been criticised for incomplete disclosure of trial designs (5). Vaccine approvals by the Indian drug regulator did not follow established pathways and decision-making processes were opaque (6).…”
Section: Introductionmentioning
confidence: 99%
“…concluded in their study that at 12 weeks, 87.0% of females experienced a decrease in pain score <3, while Gandhi A demonstrated that pain steadily decreased over 3 months of Centchroman treatment (from 5.8 to 0.86). [ 14 15 ] Additionally, in this study, the number of mastalgia patients experiencing tender nodularity after treatment was significantly lower in the Centchroman group (11.8%) compared to the evening primrose oil group (44.4%) ( P = .035).…”
Section: Discussionmentioning
confidence: 50%
“…On follow up for 6 months, 83.92% were symptom free. 9 Rathi et al show centchroman significantly alleviated mastalgia with minimal side effects. Overall patients reporting to be pain free at 12 weeks were 88 and 85% at end of 24 weeks.…”
Section: Discussionmentioning
confidence: 99%